Imatinib – an overview (Hematology Meeting Reports, 2009)
Historical perspective and chemical development The potential of Abl kinase inhibitors for the treatment of Abl-related leukemias was suggested as early as 1989.1 Several tyrphostins, a series of compounds derived from the erbstatin, an inhibitor of the epidermal growth factor receptor were shown to be potent and rather specific inhibitors of Bcr-Abl, with biological activity in cell lines derived from patients with chronic myeloid leukemia (CML).2 Tyrphostins were however not developed clinically. Imatinib, the first clinically viable Abl kinase inhibitor, is the result of a medicinal chemistry project initiated by Ciba Geigy (now Novartis) in the early 1990s, with protein kinase C as the initial target. During this project, a 2-phenylaminopyrimidine derivative was identified as the lead compound.3,4